Supplementary dataset to the article "Exploring Soil Microbiota Functionality using a Soil Quality Index to Assess the Impact of Cover Crops" [Conjunto de datos] - Campilongo Mancilla, Ernesto Javier; Serri, Dannae Lilia; Bernardi Lima, Nelson; Gabbarini, Luciano; Córdoba, Mariano; Quiroga, María; Barbero, Florencia; Meriles, Jose Manuel; Vargas Gil, Silvina (Instituto de Patología Vegetal (IPAVE), INTA, 2025)
Tabla con variables medidas en los suelos. GRSP, Glomalin-related soil protein; Variable continua. MBC, soil microbial biomass carbon; Variable continua. MR, Soil microbial respiration; Variable continua. FDA, fluorescein diacetate activity; Variable continua. pH, Soil pH; Variable continua. SOC, soil organic carbon; Variable continua. N, soil total nitrogen; Variable continua. eP, soil total phosphorus; Variable continua. LEU, leucine aminopeptidase; Variable continua. PHOS, acid phosphatase; Variable continua. XYL, β-D-xylopyranosidase; Variable continua. CEL, β-D-cellobiosidase; Variable continua. GLR, β-D-glucuronidase; Variable continua. NAG, β–1,4–N–acetylglucosaminidase; Variable continua. GLC, β–glucosidase; Variable continua. LOTE; Variable categorica. CC_ID; Variable categorica. Cultivo; Variable categorica. Sitio; Variable categorica. Bloque; Variable categorica.